Prognostic factors for success in the Kangaroo Mother Care method for low birth weight babies - Rina Pratiwi; Muhammad Sholeh Kosim; Noor Wijayahadi (Indonesian Pediatric Society, 2015)
Background Low birth weight (LBW) is closely related to neonatal morbidity and mortality. Management of LBW infants in developing countries remains limited, due to the low availability of incubators. The Kangaroo Mother Care (KMC) method has been shown to be effective for newborns, especially LBW infants, in which skin-to-skin contact may be conducive for infants’ weight gain, thermoregulation, and heart rate stability.Objective To determine the prognostic factors for KMC success in LBW babies.Methods This cohort study included LBW infants at Dr. Kariadi General Government Hospital, Semarang, by a consecutive sampling method. Success of KMC was assessed by infant weight gain, as well as stabilization of temperature, heart rate, and respiration. Prognostic factors for KMC success that we assessed were birth weight, gestational age, KMC duration, age at KMC onset and maternal education level. Statistical analyses used were Chi-square and relative risk (RR) tests.Results Of 40 LBW infants, 24 were successful in KMC. Birth weight ≥ 1500 grams (RR 0.4; 95%CI 0.23 to 0.73; P=0.001)], gestational age ≥ 34 weeks (RR 0.94; 95%CI 0.46 to 1.89; P=1.00), KMC duration ≥ 65 minutes (RR 1.44; 95%CI 0.76 to 2.75; P= 0.215), high maternal education level (RR 1.25; 95%CI 0.76 to 2.04; P=0.408), and age at KMC onset >10 days (RR 2.69; 95%CI 1.14 to 6.32; P=0.003), were factors that related to the successful of KMC.Conclusion Age at KMC onset > 10 days was a prognostic factor for KMC success in low birth weight babies.